The Effect of Headset and Earphone on Reducing Electromagnetic Radiation from Mobile Phone toward Human Head - Dayang Azra, Awang Mat; Kho, Franky; Joseph, A.; Kipli, K.; Sahrani, S.; Lias, K.; Ade Syaheda Wani, Marzuki (IEEE, 2010)
Studies show that exposure to the electromagnetic wave for a certain period of time will leads to health problem such as headaches, or even worse, brain cancer. Scientist have known that this radiation might cause human biological damage through heating effects since human body is made up of approximately 65-70% water, electrolytes and ions. Radio frequency radiation emitted from mobile phone will interact with human body and interfere with human body’s natural healing resulted displacement of electrolytes and ions within the body. This paper discussed on the analysis conducted to study the effect of electromagnetic radiation (thermal radiation) of mobile phones with different frequencies via experimental works. The experiment was conducted in a laboratory using a volunteer (human). The period of operation is 45 minutes as the talking time on the phone. Thermal imaging technique is used to monitor and capture the temperature distribution during the experimental analysis for every 5 minutes interval. Images will be collected and analyzed using graphical plot. Devices such as Bluetooth headset and earphone are also used to study either this equipment are effective to reduce the effect of thermal radiation toward human head or not. The result shows that mobile phone serving GSM 900MHz has the highest temperature increment compare to mobile phone serving GSM 1800MHz. It is also shown that GSM 900MHz has greater thermal radiation effect or heating effect. By using Bluetooth headset and earphone device when talking via mobile phone, the result shows lower radiation since direct radiations from the mobile phone antenna was reduced